Disaster communication in the digital age: a community-based case study of media, education, and local knowledge in Pangandaran, Indonesia - Rizal, Edwin; Winoto, Yunus; Sugito, Toto; Nugroho, Catur; Septian, Falih I. (Frontiers in Communication, 2025)
In disaster-prone regions such as Pangandaran Regency, Indonesia, effective communication is essential for mitigating risk and enhancing community preparedness. This study examines how digital media, disaster education, and localized communication strategies contribute to developing disaster mitigation information literacy and resilient community behaviors. Using a qualitative case study approach, researchers collected data through 10 semi-structured interviews and a focus group discussion involving key stakeholders, including disaster response officers, educators, community leaders, and local volunteers. Thematic analysis explored perceptions, barriers, and practices related to disaster communication and preparedness. Supplementary field observations and document reviews supported triangulation. Findings reveal that digital platforms like WhatsApp and Facebook have become central channels for risk information dissemination. However, they also present challenges due to misinformation, connectivity gaps, and limited institutional presence online. Traditional warning systems, such as sirens and signage, are deteriorating due to maintenance issues, further complicating message delivery. In contrast, informal networks, local knowledge, and school-based disaster education initiatives have significantly shaped public understanding and response behavior. The study highlights a disconnect between formal communication infrastructures and community-based practices, revealing a need to integrate digital media with culturally rooted communication models. This research offers a novel contribution by bridging modern digital tools, formal education efforts, and indigenous knowledge in one framework—an integrative approach largely absent in previous disaster communication studies. Trust-building, media literacy, and familiar community intermediaries emerge as critical for improving disaster communication efficacy. Communication strategies must embrace a multi-channel, participatory, and culturally adaptive approach to strengthen coastal communities’ disaster mitigation literacy and preparedness. Bridging digital and traditional knowledge systems is key to fostering community resilience in the face of increasingly complex disaster risks.